Influence of polyphenol-rich diet on exercise-induced immunomodulation in male endurance athletes - Lackermair, K.; Scherr, J.; Waidhauser, G.; Methe, H.; Hoster, E.; Nieman, D. C.; Hanley, A.; Clauss, S.; Halle, M.; Nickel, T. (Applied Physiology, Nutrition, and Metabolism, 2017)
Stress is associated with increased susceptibility to infection. We investigated if the mechanism involves immunomodulation of dendritic cells and whether this can be inhibited by a polyphenol-rich diet. Blood samples were taken from a total of 100 male endurance athletes at 5 time points around a marathon run: 4 weeks before; 1 week before; and immediately, 24 h, and 72 h after. Participants were randomized into 2 double-blinded groups. One group received a polyphenol-rich beverage during a 3-week training phase before marathon while the other group received a placebo beverage. Flow cytometric analysis of dendritic cell (DC) counts and subpopulation counts (myeloid, plasmocytoid DCs) was performed. Levels of viral antigen presenting toll-like receptor (TLR) 7 messenger RNA was measured by real-time polymerase chain reaction. Marathon running induced a significant increase of circulating myeloid DCs (0.2% vs. 0.33% of whole-blood leukocytes (wbl); p < 0.01) and a significant decrease of plasmozytoid DCs (0.12% vs. 0.03% of wbl; p < 0.01) and TLR7 expression (decline of 60%; p < 0.01). Polyphenol supplementation did not significantly affect mobilization of dendritic cells but showed beneficial effects on regeneration of TLR7 expression in wbl at 3 days postmarathon (decline of 40% vs. increase of 1000%; p < 0.05). In conclusion, physical stress affects circulating DCs, with an increase of myeloid and a decrease of plasmozytoid DCs. This may partially explain the susceptibility to viral infections after strenuous exercise. These detrimental effects are not attenuated by polyphenol supplementation. However, polyphenols support regeneration of viral antigen presenting TLR7 after strenuous exercise.